Pengaruh Penggunaan Metode Cooperative Integrated Reading and Composition (CIRC) terhadap Keterampilan Literasi Informasi ditinjau dari Hasil Belajar Sejarah Siswa - Ila Samsiah; Yani Kusmarni (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
This research was motivated by the low information literacy skills of students. This can be seen from the low skills of students in finding, processing, and presenting information. These skills can be seen through learning outcomes, because learning outcomes are a measure of the success of the learning process. Therefore, this study entitled "The Effect of Using the Cooperative Integrated Reading and Composition (CIRC) Method on Information Literacy Skills in terms of Student Learning Outcomes in History Learning (Quasi Experimental Research at Class X SMA Negeri 9 Bandung). The CIRC method is used in the experimental class by dividing students into small groups, which then each finding, processing, and presenting information, as well as making answers to problems. This study was conducted to examine the effect of using the Cooperative Integrated Reading and Composition (CIRC) method on information literacy skills in terms of student learning outcomes in history learning. The method used in this research is a quasi-experimental method with one group time series design. The research was conducted at SMA Negeri 9 Bandung. The instrument used to obtain data in the study was a written test in the form of multiple choice questions and a questionnaire. Based on the data obtained from the results of the calculation of the hypothesis test, the Sig. 0.004 0.05 so that Ho is rejected and Ha is accepted so that there is an effect of using the CIRC method on information literacy skills both for groups of students who have information literacy skills "Good", "Good Enough" and “Not Good”. Meanwhile, the results of the pretest and postest statistical tests show that there were differences in learning outcomes for groups of students who had information literacy skill “Good”, “Good Enough, or “Not Good before and after using the CIRC method. This can be seen from the increase in the average pretest-postest score and the gain index of each experimental class.